2019
DOI: 10.1007/s12040-019-1265-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of particulate matter at a high-altitude site in southwest India: Impact of dust episodes

Abstract: Observations on a particulate matter (PM 10 and PM 2.5) were carried out during March 2015 to February 2017 over a high-altitude location Mahabaleshwar in the Western Ghats region in southwest India. Apart from temporal variation of PM and the ratio of PM 2.5 /PM 10 , impacts of local meteorological parameters on the concentration of PM are examined. PM 10 showed a maximum concentration during pre-monsoon, whereas PM 2.5 showed it in winter. The monsoon season showed the lowest concentrations for both PM 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…A similar impact of mountainvalley circulations on air pollution was observed by Bei et al (2018). Studies at high-altitude sites in southwestern India have also found that diurnal variations of aerosol particle concentrations were related to mountain-valley winds and the variation in planetary boundary layer height (Buchunde et al, 2019).…”
Section: Mechanism Of Day-night Variationsupporting
confidence: 62%
See 1 more Smart Citation
“…A similar impact of mountainvalley circulations on air pollution was observed by Bei et al (2018). Studies at high-altitude sites in southwestern India have also found that diurnal variations of aerosol particle concentrations were related to mountain-valley winds and the variation in planetary boundary layer height (Buchunde et al, 2019).…”
Section: Mechanism Of Day-night Variationsupporting
confidence: 62%
“…There is increasing interest in atmospheric aerosol studies at high-altitude sites. Studies have investigated the aerosol chemical composition in mountainous regions, highlighting the influence of mountain valleys, nighttime mountain breeze, and topography in dispersing polluted air masses to the free troposphere (Zhang et al, 2009;Alastuey et al, 2005;Buchunde et al, 2019;Leena et al, 2017;Glasius et al, 2018;Lugauer et al, 1998;Mukherjee et al, 2020). Furthermore, other studies at the northeastern Himalayas, India (Chatterjee et al, 2010), the Bachelor Observatory Mountain in Oregon, USA (Ambrose et al, 2011), and a mountain site at Lulang on the southeastern Tibetan Plateau, China (Zhao et al, 2013), have reported the importance of the aerosol chemical composition at mountain sites in the identification of potential source regions of anthropogenic pollutants and their mechanism of transport.…”
Section: Introductionmentioning
confidence: 99%
“…A similar impact of mountain-valley circulations on air pollution was observed by Bei et al (2018). Studies at high-altitude sites in southwest India, also found that diurnal variations of aerosol particle concentrations were related to mountain 795 valley winds and the variation in a planetary boundary layer height (Buchunde et al, 2019).…”
Section: Mechanism Of Day-night Variationmentioning
confidence: 92%
“…Based on the data collected at HACPL by the various in-situ instruments, some studies in the past performed to understand cloud-aerosol interaction over the Western Ghats (Anil Kumar et al, 2016;Buchunde et al, 2019;Das et al, 2017Das et al, , 2020Jayachandran et al, 2018;Konwar et al, 2010Konwar et al, , 2014Krishna et al, 2021;Kumar et al, 2022;Kumar & Silva, 2019;Leena et al, 2016Leena et al, , 2018Leena et al, , 2021Mukherjee et al, 2018;Singla et al, 2017;Sumesh et al, 2019Sumesh et al, , 2021Utsav et al, 2017;Varghese et al, 2021;. To study the diurnal variation of DSD, we use an impact-based disdrometer, i.e., Joss-Waldvogel Disdrometer (JWD) (Joss & Waldvogel, 1969) measurements during the Indian Summer Monsoon (ISM: June, July, August and September month) period between 2015 and 2019 at the HACPL, Mahabaleshwar, which is situated in the windward side of the Western Ghats in India.…”
Section: Joss-waldvogel Disdrometermentioning
confidence: 99%